2018
DOI: 10.7251/agren1703155n
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Summer Pruning Operations on the Winter Buds Productivity of cv. Vranec (Vitis vinifera L.)

Abstract: The study presents the analysis of the influence of summer pruning operations (defoliation, cluster thinning) on the parameters of a potential productivity of winter buds at the vine variety Vranec grown near Veles in the period 2013-2015. For this research, four treatments were set: control, defoliation and two types of cluster thinning: 10 and 6 clusters per vine. From the obtained results it is found that there are no injuries in the main winter buds during the vegetation period and the potential fruitfulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Working on Sangiovese, Storchi e Mattii [5] reported that photosynthetic activity and leaf water potential were greater at higher altitudes while no effect on total soluble solids was found. Little information is available on the mechanical properties of the berries; Nedelkovski et al [6] report that the different altitudes did not have a significant effect on the epidermal layer thickness. Contrarily, more than a few studies have examined the effects of vineyard altitude on phenolic and aromatic compound in grapes and wines from different vine growing areas.…”
Section: Introductionmentioning
confidence: 99%
“…Working on Sangiovese, Storchi e Mattii [5] reported that photosynthetic activity and leaf water potential were greater at higher altitudes while no effect on total soluble solids was found. Little information is available on the mechanical properties of the berries; Nedelkovski et al [6] report that the different altitudes did not have a significant effect on the epidermal layer thickness. Contrarily, more than a few studies have examined the effects of vineyard altitude on phenolic and aromatic compound in grapes and wines from different vine growing areas.…”
Section: Introductionmentioning
confidence: 99%